Configurações estratégicas de empresas de alto desempenho: análise qualitativa comparativa das imperfeições de mercado por elas exploradas. - Gurgel, Maria Cristina Barbosa do Amaral (2011)
The objective of this work was to identify the strategic configurations of high performance Brazilian companies, based on the market imperfections they explore. This study shows that Brazilian firms with high performance are exposed to competitive conditions of special nature and character not all of which are covered by the types of competition - Industrial Organization, Chamberlinian or Shumpeterian - described by Barney (1986). The research metodology combines (1) MDSO (Most Different Similar Outcome) approach of Qualitative Comparative Analysis (QCA) to find organizational configurations with (2) Semantic and Categorical Content Analysis for exploring reports on the companies of interest produced by stock broking firms and investment banks.